The Impact of Innovative Marketing on Performance of Mobile Money Enterprises in the Telecommunication Industries in Cameroon - Tamfuh, Kimbi Boris (Digital Repository of Theses, 2026)
The importance of micro, small and medium sized enterprises to all nations cannot be overemphasized. Micro, small and medium (SME) sized enterprises play a vital role in the growth of the economies of many nations, Cameroon inclusive. These enterprises are a major source of employment in many developing nations. The micro-entrepreneurs in the mobile telecommunications sector face numerous challenges, including inadequate cash flow, a lack of marketing expertise, escalating competition, customer-related issues, and an unfavorable business environment. As such, the objectives of this study were; To assess contribution of digital marketing, one-on-one marketing, influencer marketing campaign, and mobile money app-base marketing practice to revenue generation and market share of micro mobile money enterprises. Materials and Methods: A community based cross-sectional mixed study design on the impact of Innovative Marketing on the Performance of Micro Enterprises was conducted across seven regions in Cameroon, questionnaires and interview quid were use to capture data. Beginning with the quantitative design, SPSS version 26 was used for the analysis. Results were presented using percentages, frequency tables and graphs. Statistical analysis such as chi-square test and regression was utilized to analyze the collected data and determine the impact of innovative marketing on enterprise performance. Results:The results show that digital marketing relates negatively and significantly, at 1% (p<0.01), to the performance of micro enterprises in the mobile money industry. The coefficient for the "One-on-one marketing index" is 0.251 and was found to be statistically significant (p <0.01), suggesting a positive relationship. Specifically, an improvement in the one-on-one marketing is associated with a 0.251 unit increase in the performance of these enterprises, holding all other variables constant. Furthermore, the influencer marketing index demonstrates a strong positive association (coefficient = 0.264, p < 0.01), indicating that businesses utilizing influencer marketing tend to report higher levels of performance. The mobile app marketing index demonstrates a statistically significant positive effect (coefficient = 0.215, p < 0.01), indicating that businesses employing mobile app marketing strategies tend to report higher performance levels compared to those who do not. Conclusion:The study revealed a mixed picture of innovative marketing's impact. While one-on-one marketing and influencer marketing campaigns showed a significant positive influence on enterprise performance (p<0.01), digital marketing, particularly social media's contribution to overall revenue growth, was less definitively perceived by respondents, with a notable negative correlation found between a digital marketing index and performance outcomes (p<0.01). Mobile money app-based marketing also demonstrated a remarkably positive influence on performance (p<0.01). Keywords: Digital Marketing, Mobile Money, Social Media, One-on-One Marketing, Influencer Marketing.